2017
DOI: 10.1136/bmjopen-2016-015327
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of public hospitals in Nepal: a data envelopment analysis

Abstract: ObjectivesPublic hospitals in Nepal account for a major share of the total health budget. Therefore, questions are often asked about the performance of these hospitals. Existing measures of performance are limited to historical ratio analyses without any benchmarks. The objective of this study is to explore the trends in inputs, outputs and productivity changes in Nepalese public hospitals from 2011–2012 to 2013–2014.Setting and participantsThe study was conducted among 32 Nepalese public hospitals (23 distric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
(17 reference statements)
0
8
0
7
Order By: Relevance
“…Since this deterioration in TFP is primarily accounted for by technical regress, the solution to realise productivity growth among hospitals in the KSA is technical progress. To achieve such technical progress (innovation), the requirement is investment in more or better machinery, equipment, and structures that will make it possible for hospitals to produce greater output [ 16 , 32 ]. Other studies have found that productivity growth can be achieved by raising physician productivity, which is in turn dependent on the compensation mechanism [ 17 , 36 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this deterioration in TFP is primarily accounted for by technical regress, the solution to realise productivity growth among hospitals in the KSA is technical progress. To achieve such technical progress (innovation), the requirement is investment in more or better machinery, equipment, and structures that will make it possible for hospitals to produce greater output [ 16 , 32 ]. Other studies have found that productivity growth can be achieved by raising physician productivity, which is in turn dependent on the compensation mechanism [ 17 , 36 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The set of outputs generally includes the numbers of inpatient visits, outpatient visits, surgical operations, laboratory investigations, radiology films, and patients; bed turnover rate; bed occupancy rates; and average length of stay [ 7 , 15 ]. Some studies adjusted for the case-mix and complexity of surgical procedures [ 14 , 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the temporal changes in technology, in terms of the operational management of the respective inputs and outputs, provide an opportunity for DMUs to optimise their efficiency. In Nepal, Silwal and Ashton [76] notes the potential for hospitals to increase their outputs given the additional resources through the years. While in Greece, Polyzos [77] observed that middle-sized hospitals were able to achieve 100% technical efficiency in the span of 2009–2011 as a result of technological changes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…While maternal and child mortality indicators have seen steady improvements over the years [ 24 ], several health challenges persist in Nepal. For instance, hospital care is only free for people in verified poverty situations and other vulnerable groups [ 25 , 26 ], leaving a substantial share of the population paying out-of-pocket for health care. On Saturday, 25 April 2015, a high-magnitude earthquake Nepal, followed by many aftershocks, a major one on May 12 th .…”
Section: Methodsmentioning
confidence: 99%